PENGARUH KONSEP DIRI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA BARU - Anggreni, Ni Luh Putu Yesy; Cahayani, Ni Luh Putu (Widyadari : Jurnal Pendidikan, 2019)
Entrepreneurial interest is one's desire to start trying, create jobs according to their own will without coercion from others. Interest grows slowly in a person according to what is seen in his environment. The main goal of entrepreneurship is to create jobs for yourself, which will then have an impact on other job seekers. Growing interest requires a strong self-concept and a supportive family environment, especially in entrepreneurial activities. The tight competition in the world of work causes more unemployment in society. So to overcome this it is deemed necessary to foster interest in entrepreneurship. The study with the title "The influence of self-concept and family environment on New Student Entrepreneurial Interest" aims to find out: (1) To find out the significant effect of Self Concepts on New Student Entrepreneurial Interest in Economics Education Study Program FPIPS IKIP PGRI Bali, (2) To determine the effect Significant Family Environment on Entrepreneurial Interests of New Students in the FPIPS IKIP PGRI Bali Economic Education Study Program, and (3) To find out the significant influence of the Self-Concept and Family Environment together on New Student Entrepreneurial Interest in the Economic Study Program of FPIPS IKIP PGRI Bali. The data analysis technique used is two predictor linear regression, Based on the results of data analysis and discussion, it can be concluded that the results of the study are as follows: 1) Self-Concept (X1) has a positive and significant effect on Entrepreneurial Interest. This is evidenced by the value of t-count = 3.990> t-table = 2.00 and Sig. = 0,000 <0.05. 2) Family Environment (X2) has a positive and significant effect on Entrepreneurial Interest. This is evidenced by the value of t-count = 3.236> t-table = 2.00 and Sig. = 0.002 <0.05. 3) Self Concept (X1) and Family Environment (X2) simultaneously influence the Entrepreneurial Interest. This is evidenced by the calculated F-value = 34.561> F-table = 3.14 and Sig. = 0,000 <0.05. Based on the results of the analysis above, it is expected that lecturers and faculty leaders will motivate students more in entrepreneurial activities. This will have a positive impact on students. Students can study or start entrepreneurship as early as possible.